Three M syndrome 2 in two Indian patients. Issue 2 (1st November 2020) - Jacob, Prince; Girisha, Katta M.
Abstract: 3‐M syndrome is a rare autosomal recessive disorder, characterized by short stature, characteristic facies and absence of microcephaly and intellectual disability. 3‐M syndrome 2 (MIM# 612921) is caused by biallelic disease causing variants in OBSL1 . In this study, we identified two probands from two families with homozygous, c.1534 + 5G > T and compound heterozygous variants, c.35dup and c.1273dup in OBSL1, respectively. We herein highlight the clinical and molecular findings of the first reported cases from Indian ethnicity.